Oxford Handbooks Online 2013
DOI: 10.1093/oxfordhb/9780199730445.013.030
|View full text |Cite
|
Sign up to set email alerts
|

The Social Embeddedness of Organized Crime

Abstract: and KeywordsBetween organized crime and the legitimate societal context, there are usually all sorts of "interfaces," and the relationships between legality and illegality are by no means necessarily antagonistic or aimed at avoiding one another. Instead of operating in a social vacuum, organized crime has a habit of interacting with its social environment. This contribution aims to develop the perspective of the social embeddedness of organized crime. It focuses on the embeddedness of organized crime with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
(18 reference statements)
1
34
0
Order By: Relevance
“…A meta-analysis by Besemer et al (2017), which compares 23 datasets including 3.5 million children, shows that children with one or more convicted parents have a 2.4 times higher risk of being convicted themselves. We know that within serious and organised crime networks, families play an important role, for instance because family ties provide trust relations (van de Bunt et al 2014). Generation studies of families involved in organised crime are almost nonexistent, however.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Besemer et al (2017), which compares 23 datasets including 3.5 million children, shows that children with one or more convicted parents have a 2.4 times higher risk of being convicted themselves. We know that within serious and organised crime networks, families play an important role, for instance because family ties provide trust relations (van de Bunt et al 2014). Generation studies of families involved in organised crime are almost nonexistent, however.…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated in the Montréal cases that illustrated a symbiotic relationship between criminal groups and collusive business owners (cf. Gambetta and Reuter 1995;Passas 2002;van de Bunt et al 2014). In the Dutch inclusive system, there is less of a natural need for a strong arm to enforce the existing power balance of construction firms in the industry.…”
Section: Resultsmentioning
confidence: 99%
“…Building on this, Ruggiero (1996) purposes a joint analysis using organisational theory for the often conceptually distinguished phenomena of white-collar and organised crimes. Social networks around serious crimes for gain are known to involve interactions between 'licit' and 'illicit' services and 'formal' and 'informal' economies (Passas 2002;van de Bunt et al 2014;Lippens & Ponsaers 2006;Ruggiero 1997;van Duyne 1995van Duyne , 1996. Different types of relationships between organised crime and legitimate business, or upper-and underworld are distinguished (van Duyne et al 2002).…”
Section: Government Replacement and Protection Theorymentioning
confidence: 99%
“…Or does it make them more vulnerable to suspicion and detection? An alternative explanation is that neither isolation nor exclusion but the social embeddedness of crime and criminal networks protects its members against detection [30,56,57]. Scholars have suggested that most crime is committed within an informed and even cooperative social environment [58,59].…”
Section: Criminal Network and Social Embeddednessmentioning
confidence: 99%
“…In other words, to answer the question how cartels succeed in hiding their activities from outsiders for long periods of time, the relation of the cartel and its participants with their social environment is also important. In the existing literature, the concept of social embeddedness is used to describe this process [51,52,57]. Social embeddedness entails both structural and relational embeddedness.…”
Section: Criminal Network and Social Embeddednessmentioning
confidence: 99%